Gossypiboma mimicking myositis ossificans: a rare diagnostic masquerade - T. P., Meera; Raut, Sonal (International Journal of Research in Orthopaedics, 2026)
Gossypiboma refers to retained surgical material, most commonly a sponge or gauze, inadvertently left within the body after a surgical or medical procedure. Although rare, it represents an important preventable complication with potential medico legal implications. Its clinical and radiological manifestations can mimic various pathological conditions. We report the case of a 50-year-old male presenting with a swelling in the right calf associated with intermittent pain for two years. Ultrasonography revealed a heterogeneous lesion with calcifications in the deep intermuscular plane abutting the tibia, suggestive of Myositis Ossificans. Wide local excision was performed. Gross examination revealed a cystic lesion containing retained gauze material. Microscopic examination demonstrated a thick fibrous cyst wall with extensive foreign-body giant cell reaction, xanthogranulomatous inflammation, and entrapped cotton fibres, consistent with gossypiboma. This case highlights the diagnostic challenge posed by long-standing gossypiboma, which may clinically and radiologically mimic other soft tissue lesions. Histopathological examination plays a crucial role in establishing the definitive diagnosis.